2017
DOI: 10.1097/cmr.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter cohort study of cutaneous melanoma: clinical staging and potential associations with HIF-1α and VEGF expressions

Abstract: Melanoma is a highly prevalent cancer that is associated with substantial mortality. Although clinical staging procedures can serve as relatively robust prognostic indicators, we aimed to determine whether assessments of the abundance of hypoxia inducible factor-1α (HIF-1α) or vascular endothelial growth factor (VEGF) in postexcisional melanoma tumor tissues may enable more accurate determination of tumor aggressiveness. We carried out a multicenter prospective study, in which we systematically evaluated 376 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…This finding could have clinically relevant consequences, as PD‐L1/PD‐1 crosstalk has a recognized role in the development and progression of cancer of any origin . Therefore, our results could provide biological plausibility to previous reports of increased risk of cancer incidence or mortality in young patients with OSA, which disappears in older patients . Moreover, it might be argued that the concordance between this biological finding and the mentioned clinical‐epidemiological data reinforces the potential role of the PD‐L1/PD‐1 pathway in the OSA–cancer relationship.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding could have clinically relevant consequences, as PD‐L1/PD‐1 crosstalk has a recognized role in the development and progression of cancer of any origin . Therefore, our results could provide biological plausibility to previous reports of increased risk of cancer incidence or mortality in young patients with OSA, which disappears in older patients . Moreover, it might be argued that the concordance between this biological finding and the mentioned clinical‐epidemiological data reinforces the potential role of the PD‐L1/PD‐1 pathway in the OSA–cancer relationship.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, several clinical and epidemiological studies suggest that the association between OSA and cancer incidence or cancer mortality is particularly prominent in younger rather than in older patients . Specifically, a recent prospective clinical cohort study performed in our setting has shown that the independent association between OSA severity and cancer aggressiveness is particularly prominent among patients of <56 years of age . Moreover, a murine model of OSA has recently demonstrated that IH potentiates tumour progression through changes in the immune system in young mice, whereas such changes are not present in aged mice …”
Section: Introductionmentioning
confidence: 86%
“…Tumor angiogenesis is another physiological process essentially required for tumor progression and metastasis (Shi, Chen, Wang, Guo, & Wang, 2018). Although increasing evidence indicates that angiogenesis is a highly sophisticated and coordinated process, the activation of a hypoxic-induced factor (HIF) growth factor pathway remains the key modulator (Martinez-Garcia et al, 2017). Tumor tissue is usually accompanied by hypoxia, which promotes HIF production.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor aggressiveness was increased in CMM patients with OSA and long time spent at low oxygen saturation (CT90%) or high oxygen desaturation index (ODI 4%) [158, 170173]. Interestingly, tumor aggressiveness was positively associated with expression of the adhesion molecule VCAM-1 [171], HIF-1alpha [173], but not with expression of vascular endothelial growth factor (VEGF) [173]. Similar results were reported in patients with lung cancer and OSA [158].…”
Section: Common Comorbidities In Osa Patientsmentioning
confidence: 99%